Multilevel determinants of school belonging: the moderating role of national safety climate - Elizondo-González, Jose Fabián; Malla, Shreya; Barros-Bustos, Solange (Frontiers in Education, 2025)
IntroductionWhy do some students feel they belong at school while others do not? We examined how perceived school safety and teacher–student relationships relate to belonging across countries, and whether national safety modifies these links.MethodsUsing PISA 2022 data from 501,731 15-year-olds in 74 countries, we estimated multilevel models with students nested within countries. Scales for belonging, teacher–student climate, and school safety were standardized; climate and safety were decomposed into within-country (individual) and between-country (national average) components. Random slopes and cross-level interactions tested heterogeneity across contexts. Model selection used likelihood tests and information criteria.ResultsMultilevel modeling revealed that students who felt safer and more supported by their teachers reported higher belonging. Country-level differences in average safety also mattered: in safer countries, the positive link between individual safety and belonging was even stronger. However, national variation in perceived teacher–student climate was not a significant contextual predictor.DiscussionBelonging is shaped by students’ personal experiences and by national safety climate. Improving perceived safety may yield especially large gains where average safety is high, while still offering protective benefits in lower-belonging contexts. Findings highlight safety climate as a policy-relevant lever for strengthening adolescents’ connection to school across diverse settings.